ChemInform Abstract: [Cu(OH)(TMEDA)]2Cl2‐Catalyzed Regioselective 2‐Arylation of 5‐Substituted Tetrazoles with Boronic Acids under Mild Conditions. Issue 1 (January 2015) - Onaka, Takuya; Umemoto, Hideaki; Miki, Yasuyoshi; Nakamura, Akira; Maegawa, Tomohiro
Abstract A novel method for the direct coupling of tetrazoles with arylboronic acids yields 2, 5‐disubstituted tetrazoles regioselectively.